(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2021)
Bullying is a pervasive issue in nursing and other health care professional programs. As a student/faculty team at one university in Western Canada, we have created a number of initiatives within an overall project entitled Cognitive Rehearsal to Address Bullying (CRAB) that was designed to support students in managing bullying if they witnessed or experienced it during their program of study. One such initiative is the CRAB Workshop. In this paper, we describe the Workshop, which emerged in response to concerns shared by students and faculty regarding the normalized and long-standing prevalence of bullying experienced by nursing students. The Workshop brought faculty members and pre-licensure students from our school of nursing together to creatively and collaboratively address these concerns. Together with the university’s department of theatre and film, we designed an interactive educational workshop to prepare nursing students to independently identify and act on bullying witnessed or experienced in the clinical setting. In the Workshop, we engaged in forum theatre and cognitive rehearsal to foster cognitive, affective, and embodied learning. In this paper, we explain and discuss what comprised the creation and implementation of the CRAB Workshop. We address implications for future nursing education, and we offer recommendations for educators who are considering forum theatre and cognitive rehearsal as pedagogies for addressing challenging situations, such as bullying in nursing education.